2018
DOI: 10.3390/molecules23102620
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oils of Five Baccharis Species: Investigations on the Chemical Composition and Biological Activities

Abstract: This paper provides a comparative account of the essential oil chemical composition and biological activities of five Brazilian species of Baccharis (Asteraceae), namely B. microdonta, B. pauciflosculosa, B. punctulata, B. reticularioides, and B. sphenophylla. The chemical compositions of three species (B. pauciflosculosa, B. reticularioides, and B. sphenophylla) are reported for the first time. Analyses by GC/MS showed notable differences in the essential oil compositions of the five species. α-Pinene was obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 53 publications
0
48
0
1
Order By: Relevance
“…assays. Using the same methods, EO of Baccharis sphenophylla Dusén ex Malme produced 66.67 ± 3.33% mortality in the insecticide-resistant strain 'Bayonne', while producing 83.33 ± 3.33% mortality in the susceptible strain 'Ft.Dix', 24 h after treatment [53]. The EO of Schinus molle L. produced 100.0 ± 0.00% (Ft. Dix) and 90.0 ± 5.77% (Bayonne) of mortality 24 h after the treatment [54].…”
Section: Insecticidal Activitiesmentioning
confidence: 99%
“…assays. Using the same methods, EO of Baccharis sphenophylla Dusén ex Malme produced 66.67 ± 3.33% mortality in the insecticide-resistant strain 'Bayonne', while producing 83.33 ± 3.33% mortality in the susceptible strain 'Ft.Dix', 24 h after treatment [53]. The EO of Schinus molle L. produced 100.0 ± 0.00% (Ft. Dix) and 90.0 ± 5.77% (Bayonne) of mortality 24 h after the treatment [54].…”
Section: Insecticidal Activitiesmentioning
confidence: 99%
“…Glandular trichomes represent one of the types of secretory structures of aromatic plants and produce and accumulate secondary metabolites with biological activities as seen in several families such as Asteraceae (Budel et al, a, b; Pereira et al, ), Lamiaceae (Conti et al, ; Justus et al, ), and Verbenaceae (Passos et al, ). The micromorphology, number, and distribution of glandular trichomes can be useful as distinguishing features at the subfamily level of Lamiaceae (Ascensão, Marques, & Pais, ).…”
Section: Resultsmentioning
confidence: 99%
“…[18][19][20][21][22] The study also confirmed that 99% of people residing in Jeddah city had a good knowledge of bed bugs, and reported seeing them in their houses and other places, which matches reports of Potter and Doggett et al on the global resurgence of bed bugs since the beginning of the twentieth century. 23,24 The results also confirmed that there was a relation between the population density within the residential unit and recurrences of infestations by bed bugs; these were similar with the results of Doggett and Russell; Wang et al 25,26 Also, the results of the present study indicated that the highest districts infested by bed bugs were those with the highest population densities in Jeddah; those inhabited by a diversity of populations in terms of levels of living standards, their nationalities and of varying social habits and behaviour, including the districts in which migrant workers of various nationalities had settled or districts which had low levels of sanitation. These findings were compatible with outcomes reported by Copper and Wang et al and reflected the study of Sheele et al who had stated that bed bug infestations increased in cases of group housing.…”
Section: Discussionmentioning
confidence: 99%